Cognitive Behavioral Therapy for Sexual Concerns During Perimenopause: A Four Session Study Protocol - Green, Sheryl M.; Furtado, Melissa (Frontiers in Global Women's Health, 2021)
Background: During the menopausal transition, women often experience physical (e.g., vasomotor symptoms) and emotional (e.g., anxiety and depression) difficulties that significantly impact functioning and overall quality of life. Although sexual concerns are reported by up to 87% of menopausal women, treatment options that directly target this area are limited and most often involve medication. Effectiveness of these treatments is often defined as improvements in physical symptoms, however, associated psychological and emotional symptoms rarely, if at all, improve. Cognitive Behavioural Therapy (CBT) has been proposed as a low-risk treatment for menopausal symptoms with studies showing improvement in frequently reported symptoms (e.g., vasomotor symptoms, depression, anxiety, sleep). Sexual concerns, however, have either not been directly targeted or modest gains in sexual desire observed. Methods: This protocol paper outlines the development, design, and implementation of a newly developed CBT for sexual concerns trial during perimenopause (CBT-SC-Peri). The clinical sample will comprise 82 perimenopausal women aged 40 to 60 years currently in perimenopause. To ensure participants are experiencing clinically significant sexual concerns, a baseline cut-off score of 26 or lower on the Female Sexual Functioning Index will be utilized. Exclusion criteria include participants with psychotic disorders, or current substance and/or alcohol dependence, or severely depressed/suicidal. The CBT-SC-Peri is a weekly, four session treatment, lasting up to 90 minutes per session and includes psychoeducation and cognitive and behavioural strategies designed to challenge unhelpful beliefs and promote healthy sexual behaviours. Eligible women will be placed directly into treatment or on a 4-week waitlist and reassessed prior to starting treatment. Primary and secondary outcomes are assessed at baseline, post-waitlist (for those on waitlist) and post-treatment. Discussion: To our knowledge, this will be the first study to investigate the efficacy of a CBT protocol (CBT-SC-Peri) specifically aimed at improving sexual concerns experienced during perimenopause. If effective, this form of treatment may not only be preferred by some, but necessary for others as consumer demand increases for non-pharmacological treatments for perimenopausal symptoms. Further, this protocol can be integrated into perimenopausal care and will be made available by dissemination to healthcare practitioners. Clinical trial registration: Trial # NCT04922385